2015
DOI: 10.1016/j.cocom.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and mechanical properties of X2MnSn (X = Cu, Ni, Pd) under hydrostatic pressure: GGA + U calculations

Abstract: a b s t r a c tWe investigate the mechanical, electronic and magnetic properties of the full Heusler compounds X 2 MnSn (X ¼ Cu, Ni, Pd) under hydrostatic pressure using the generalized gradient approximation þ U method. We present also a comparison between the electronic and magnetic properties provided by DFT and those computed by DFT þ U in the Generalized Gradient Approximation (GGA). GGA þ U calculations show that the total magnetic moment decreases with the increase of the hydrostatic pressure, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…According to Barman et al [35], this double peak plays a crucial role in favoring martensitic transition. Moreover, we note that the ( Table III, together with available theoretical data [13,15,24,25,27,28].…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 70%
See 1 more Smart Citation
“…According to Barman et al [35], this double peak plays a crucial role in favoring martensitic transition. Moreover, we note that the ( Table III, together with available theoretical data [13,15,24,25,27,28].…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 70%
“…Mesh of 104 and 4 special Brillouin zone (BZ) k-points were used in the irreducible wedge of the BZ for the parent ternary and quaternary compounds, respectively. The cut-off energy was chosen to be - 161.02 [26] 128.5 [25] 87 [24] 145.31 [26] 14.8 [25] 5.49 [25] 158.1 [25] 137.46 [26] 81.3 [25] 138.4 [25] 8 [24] 11 [24] 158.12 [28] 128.41 [28] 92.56 [26] 81.28 [28] Ni theoretical and experimental data. Good agreement is found with the available data [13,[23][24][25][26][27][28], with the exception of the quaternary alloy.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…Specifically for cubic crystals, the only non-zero stiffness coefficients are c 11 , c 12 , and c 44 and the stability requirements are shown in Eqs. (4), (5), (6), and (7) [3, 4, 7, 14, 15, 16, 18, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49]. c11>0c44>0c11c12>0c11+2c12>0…”
Section: Main Textmentioning
confidence: 99%
“…H=true(12νtrue)E6true(1+νtrue)
Fig. 12Hardness values predicted by Yousef's approximation organized by magnetic moment (calculated from the Slater-Pauling rule) for stable Heusler alloys predicted using quantum mechanics simulations [3, 4, 7, 14, 15, 16, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,
…”
Section: Main Textmentioning
confidence: 99%
“…Rai et al, [11] showed that Cu 2 MnAl is an interesting ferromagnetic and metallic compound in spite of its non-ferromagnetic elements. Hamri et al, [12] illustrated that all the studied ferromagnetic systems X 2 MnSn (X = Cu, Ni, Pd) exhibit a metallic character and possess an interesting elastic constants. Also, Ghosh et al, [13] found that Cu 2 MnGa has metallic and ferromagnetic properties and is thermodynamically as well as mechanically stable alloy.…”
Section: Introductionmentioning
confidence: 99%